(untitled) (Community Based Medical Journal, 2018)
Prurigo nodularis (PN) is a disease with multiple itching nodules situated chiefly on the extremities. The disease is often persistent and the therapy is refractory. Oral cyclosporine used in moderate to severe psoriasis has shown modest improvement in the skin lesions with significant side effects. The drug is recently used in the treatment of PN with variable efficacy. The present study was therefore intended to investigate whether low dose oral cyclosporine can be preferred as an effective and safe therapy for Prurigo nodularis. This quasi-experimental study was conducted in the Department of Dermatology and Venereology of Community Based Medical College Hospital, Mymensingh, Bangladesh, over a period of 6 months between July 2016 to December 2016. A total of 96 clinically diagnosed cases of prurigo nodularis attending at the above mentioned places were consecutively included in the study. After evaluation of the baseline clinical and laboratory features of the patients, oral cyclosporine was given as 2 mg/kg/day for consecutive 12 weeks. A female preponderance was observed in the study with female to male ratio being 7:3. The putative etiological factors present among the patients were a history of frequent mosquito bite (43.8%), anaemia (28%), hypertension (27.1%) bronchial asthma (22.9%), family history of PN (29.2%) and family history of atopy (24%). The nodules were mainly distributed in front of the lower limbs followed by upper limbs and trunk. In terms of nodule characteristics, 33.3% were excoriated, 38.5% were palpable, 26% flattened, 28.1% infected and 35.4% pruritic nodules In the present study, majority (87.5%) of the patients became free from visible lesions after 12 weeks of treatment with cyclosporine. Serum IgE and total eosinophil count reduced significantly after treatment than those before treatment (177.5 vs. 91.6 U/mL, p < 0.001 and 0.5 vs. 0.3 k/μL, p < 0.001 respectively. However, 8.2% of the patients exhibited albuminuria during the course of treatment. Most of the patients of Prurigo Nodularis after 12 weeks of treatment with low-dose oral cyclosporine became free from the lesions without any significant side-effects. CBMJ 2018 January: Vol. 07 No. 01 P: 16-23